Implementation of the course “good chemistry: methodological, ethical and social implications” – a case study - Maciejowska Iwona (Chemistry Teacher International)
The article describes the practical implementation of the course titled “Good Chemistry: Methodological, Ethical, and Social Implications” available on the EuChemS e-learning platform. This MOOC course has been used in various ways at several European universities and through blended learning at Jagiellonian University in Krakow (Poland), which is discussed in this article. Since the groups of students participating in the course were not large and it is worth taking a closer look/insight at this issue, the case study method was used. Sample materials and activities for this course are presented. The survey responses of lecturers and students, as well as the activities and posts of Jagiellonian University in Krakow students on the remote learning platform, were analyzed. The strengths and weaknesses of the course were identified, and the need for continuous efforts by lecturers to develop ethical attitudes, critical thinking, and communication skills in students, especially in the field of socioscientific issues, was emphasized.